Pengaruh Model Pembelajaran Concept Sentence Terhadap Keterampilan Menulis Karangan Narasi Pada Siswa Sekolah Dasar - Lestari, Willa; Paida, Andi; Ayuandira, Desi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aims to determine the effect of the concept sentence learning model on narrative essay writing skills in class V UPT SDN 149 Tamalala students. This type of research is Quasi Experimental Design research and is a quantitative type of research. The sample in this study was 12 students. Data collection techniques were carried out using learning results tests and observation sheets. The data analysis technique in this research is descriptive data analysis technique and T-Test. The results of the research show that the skill of writing narrative essays before implementing the concept sentence learning model in the pretest with an average score of 59. Meanwhile in the posttest it increased with an average score of 83. Results of the t-test analysis of the influence of the concept sentence learning model on the learning outcomes of student participants The results show that the significance value obtained is good, namely the influence of the concept sentence learning model on narrative essay writing skills (Sig = 0.010) is smaller than the alpha value set, namely 0.05 (0.010 < 0.05).